2016
DOI: 10.1111/mec.13902
|View full text |Cite
|
Sign up to set email alerts
|

Canine distemper virus in the Serengeti ecosystem: molecular adaptation to different carnivore species

Abstract: Was the 1993/1994 fatal canine distemper virus (CDV) epidemic in lions and spotted hyaenas in the Serengeti ecosystem caused by the recent spillover of a virulent domestic dog strain or one well adapted to these noncanids? We examine this question using sequence data from 13 'Serengeti' strains including five complete genomes obtained between 1993 and 2011. Phylogenetic and haplotype network analyses reveal that strains from noncanids during the epidemic were more closely related to each other than to those fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 97 publications
(118 reference statements)
7
90
0
Order By: Relevance
“…Direct virus‐mediated damage and pro‐inflammatory cytokine‐induced damage to the central nervous system can also occur (Beineke et al., ). The CDV strain that infected hyenas in the 1993/1994 epidemic encoded one novel amino acid in the V‐protein (Nikolin et al., ). The V‐protein is known to disrupt host interferon signalling (von Messling, Svitek, & Cattaneo, ; Röthlisberger et al., ), hence rendering the outcome of infection particularly severe.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Direct virus‐mediated damage and pro‐inflammatory cytokine‐induced damage to the central nervous system can also occur (Beineke et al., ). The CDV strain that infected hyenas in the 1993/1994 epidemic encoded one novel amino acid in the V‐protein (Nikolin et al., ). The V‐protein is known to disrupt host interferon signalling (von Messling, Svitek, & Cattaneo, ; Röthlisberger et al., ), hence rendering the outcome of infection particularly severe.…”
Section: Discussionmentioning
confidence: 99%
“…Although adults exposed to CDV before the 1993/1994 epidemic presumably had protective antibody titres, the lack of clinical canine distemper in adult hyenas during this epidemic was probably due to other components of the immune system. Hyenas, like the domestic cat Felis catus (Beineke et al., ), can have CDV replicating in leucocytes without developing clinical disease (Nikolin et al., ). Since in long‐lived species, adult survival is a critical fitness component, natural selection may also favour the development of stronger adult immune defences to minimize the impact of infections (Boots, Best, Miller, & White, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that changes at amino acid positions 519, 530 and 549 of the H gene are associated with host specificity [18][19][20]. The host range of CDV strains and the outcome of infection depend on virus traits other than those affecting virus binding to SLAM receptors.…”
mentioning
confidence: 99%